Excitable speech: A politics of the performance - Butler, Judith (Routledge, 1997)
‘When we claim to have been injured by language, what kind of claim do we make?’ - Judith Butler, Excitable Speech Excitable Speech is widely hailed as a tour de force and one of Judith Butler’s most important books. Examining in turn debates about hate speech, pornography and gayness within the US military, Butler argues that words can wound and linguistic violence is its own kind of violence. Yet she also argues that speech is ‘excitable’ and fluid, because its effects often are beyond the control of the speaker, shaped by fantasy, context and power structures. In a novel and courageous move, she urges caution concerning the use of legislation to restrict and censor speech, especially in cases where injurious language is taken up by aesthetic practices to diminish and oppose the injury, such as in rap and popular music. Although speech can insult and demean, it is also a form of recognition and may be used to talk back; injurious speech can reinforce power structures, but it can also repeat power in ways that separate language from its injurious power. Skillfully showing how language’s oppositional power resides in its insubordinate and dynamic nature and its capacity to appropriate and defuse words that usually wound, Butler also seeks to account for why some clearly hateful speech is taken to be iconic of free speech, while other forms are more easily submitted to censorship. In light of current debates between advocates of freedom of speech and ‘no platform’ and cancel culture, the message of Excitable Speech remains more relevant now than ever.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; fem1000; performativité; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; états-unis

Présentation : du fléau social au fait social. L’étude des homosexualités - Chamberland, Line (Sociologie et sociétés, 1997)
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; cours; discipline; histoire et politique; homosexualité; identités LGBTQIA2+; militance; premier cycle; périodes historiques; sciences humaines; sciences sociales; sex1183; sexualité; soc2014; sociologie; thématiques

Le processus de reconstruction des réseaux sociaux des femmes immigrantes dans l’espace montréalais - Chicoine, Nathalie; Charbonneau, Johanne; Rose, Damaris; Ray, Brian (Recherches féministes, 1997)
Le processus d'émigration produit un profond bouleversement des liens interpersonnels. L'arrivée dans un nouveau pays oblige à une reconstruction souvent presque complète des réseaux de sociabilité et d'entraide. Par l'entremise de l'étude des communautés ethniques, des chercheurs et des chercheuses ont mis en évidence l'importance des affinités ethnoculturelles dans la création des réseaux personnels après l'arrivée dans un nouveau pays. Cependant, ces travaux se sont rarement attardés sur la reconstruction du processus même de création des réseaux à partir d'expériences individuelles. En 1996, notre équipe a réalisé une enquête auprès d'immigrantes d'origine latino-américaine, polonaise et indienne, arrivées à Montréal entre 1988 et 1991 et mères de jeunes enfants. À l'aide d'instruments d'enquête quantitatifs et qualitatifs, nous avons retracé l'histoire de la construction du réseau social de ces femmes depuis leur arrivée au pays, à travers l'analyse des événements familiaux, résidentiels et professionnels vécus au cours de ces années. Nous présentons ici une synthèse du processus de création des réseaux sociaux de ces femmes et analysons en particulier l'influence de certains facteurs sur ce processus tels que l'origine ethnique, la proximité résidentielle et le vécu d'événements particuliers.
Keywords: 1900-1999; 1990-1999; amériques; cours; discipline; environnement; femmes immigrantes; périodes historiques; québec; régions géographiques; réseau social; sciences humaines; soc1061; sociologie; thématiques

L’organisation du travail dans des groupes de femmes - Fournier, Danielle; Guberman, Nancy; Beeman, Jennifer; Gervais, Lise (Nouvelles pratiques sociales, 1997)
À partir des données préliminaires d'une recherche en cours sur la culture organisationnelle des groupes de femmes, nous verrons en quoi leurs valeurs et leurs pratiques organisationnelles pourraient apporter une contribution importante aux réflexions actuelles sur les transformations de l'organisation du travail. L'article qui suit se divise en trois sections traitant : 1) de la méthodologie de la recherche; 2) de l'organisation du travail dans les groupes, du contrôle sur le processus du travail et de l'humanisation des rapports de travail; 3) de certains paradoxes découlant de cette organisation du travail.
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; canada; discipline; groupes de femmes; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail; travail social

Visibles et Partenaires: recherches et pratiques féministes - Garceau, Marie-Luce (Reflets: Revue ontaroise d'intervention sociale et communautaire, 1997)
Visibles et Partenaires est un colloque sur les pratiques et les recherches féministes en milieu francophone qui s’est tenu les 8, 9 et 10 mai 1997 à l’Université Laurentienne, Sudbury. Cet événement mémorable a regroupé plus de deux cents femmes de toutes les régions de l’Ontario et d’ailleurs. Plus d’une cinquantaine de conférencières provenant des milieux communautaires, universitaires et professionnels ont pris la parole et échangé avec les participantes. Visibles et Partenaires a été une occasion unique d’analyser divers aspects de la réalité des Franco-Ontariennes. Les femmes présentes ont pu partager leurs points de vue, leurs expériences, leurs savoirs. De plus, ce colloque a permis le développement de partenariats stratégiques axés sur l’action et les changements sociaux. Ce numéro de Reflets est consacré à quelques-unes des conférences qui ont été présentées lors de ce colloque.
Keywords: 1900-1999; 1990-1999; OFDIG; amériques; construction du savoir; discipline; femmes*; francophonie; ontario; périodes historiques; recherche partenariale; ressource en ligne; régions géographiques; savoir féministe; sciences humaines; travail social; épistémologie

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation in the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; discipline; ethnographie; genre; harcèlement sexuel; masculinisme; montréal; mémoires/thèses; nouvelle-orléans; patriarcat; philosophie; périodes historiques; régions géographiques; résistance; san francisco; sciences humaines; systèmes d'oppressions; thématiques; violences

Killing the Black Body: race, reproduction, and the meaning of liberty - Roberts, D. (Pantheon, 1997)
Keywords: 1900-1999; 1980-1989; 1990-1999; afro-féminisme; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; histoire et politique; inégalités; justice reproductive; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis